Diagnosis and proposals for municipal solid waste Professor Jamil, GO - Ferreira, Evaldo de Melo (2015)
The main objective for the completion of this work has been to propose measures to mitigate possible contamination generated by the disposal, carried out in the diagnosis carried out, as well as technological routes for waste. Technological routes identified in this work aimed at alternatives to reduce the volume of waste being sent to landfill. One of the main tools used to assess the area was the Quality Landfill Index (QLI) proposed by Companhia Ambiental do Estado de São Paulo (CETESB) where the dump got average score of 1.5 on a scale of 0 to 10. The QLI considers local characteristics, infrastructure and operational conditions. In the QLI for the implementation of this work were made bibliographic survey related to the topic and also the determination of gravimetric composition of the waste generated in the city. In this last step, the following groups were considered: organic matter, metal, paper, plastic, fabric and other unidentified ma terials. With expected, due to population habits, the item with the highest percentage was organic matter, corresponding to 68.2% of the total. During the execution of this work, Professor Jamil was under review for holding consortium.